Production of tomato seedlings using seeds pelleted with Natrum muriaticum and submitted to saline stress - Bonfim, Filipe Pereira Giardini [UNESP]; Casali, Vicente Wagner Dias; Yoshikawa, Aline Mako [UNESP] (My University, 2019)
The development and yield of plants is directly related to the effects of salinity. There are several reports in scientific studies of significant reduction in the growth and production of tomato in soils with high electrical conductivity. The correction or recovery of salinized soils, although technically possible, is a slow and very expensive process, making it necessary to develop new technologies. The objective of this study is to evaluate the production of tomato (Solanum lycopersicon L.) seedlings using seeds pelleted with a homeopathic preparation of Natrum muriaticum (Nat-m) submitted to saline stress. The treatments consisted of the pelletization of tomato seeds with six dynamizations of Nat-m (3cH, 5cH, 7cH, 9cH, 11cH and 13cH). Coated or uncoated seeds (controls) were placed in phenolic foam blocks, kept in plastic trays previously moistened with 50 mM NaCl saline solution (2.922 g.L-1 of NaCl, electrical conductivity = 4.5 dSm-1) and nutrient solution (0.15 dS.m-1) at half the ionic strength, containing 4, 1, 2, 1, 0.5, and 0.5 mmol.L-1 of N, P, K, Ca, Mg and S, and 17.5, 9.5, 10.5, 2, 0.45 and 0.35 mmol.L-1 of Fe, Mn, Zn, Cu and Mo, respectively. The variables evaluated were percentage of emerged plants, emergence speed index, shoot length, leaf area, number of leaves, root volume, root dry matter, and shoot dry matter. The treatments pelleted seeds/talc Nat-m 5cH and pelleted seeds/talc Nat-m 7cH increased all variables evaluated. They differed statistically from the controls, with a positive response for the development of tomato seedlings under disequilibrium conditions.
Keywords: Homeopathic preparations; Homeostasis; Pelletization; Salinity; Solanum lycopersicon